EFEKTIVITAS MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA PROMOSI DESA WISATA WAE REBO - Hartono, Frenandino Axelarios Caino; Suryawan, Ida Bagus; Sukana, Made (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
In the current digital era, tourism promotion through Instagram social media has become an effective strategy to introduce tourist destinations to a broader audience. Promotion is considered effective when it succeeds in achieving its intended goals. To assess the effectiveness level of a promotional medium, an in-depth measurement of its effectiveness is necessary. This research aims to measure and assess the effectiveness of Instagram @waerebo.official as a promotional medium for the Wae Rebo Tourism Village using the EPIC Model, which consists of empathy, persuasion, impact, and communication. The measurement of promotional effectiveness through the EPIC model method is conducted by first calculating the average values of the empathy, persuasion, impact, and communication dimensions. Subsequently, the EPIC rate value is determined to evaluate how effective the promotion has been. Data collection techniques include observation, interviews, questionnaires, and literature review. The sampling technique used in this research is convenience sampling, with a total of 98 respondents. Data analysis uses descriptive statistical analysis with a quantitative approach, including validity testing, reliability testing, and analysis through the EPIC model. The research results indicate that the promotion was considered effective, with an EPIC rate score of 4.10. The empathy dimension achieved an average score of 4.30 (very effective), the persuasion dimension scored an average of 4.11 (effective), the impact dimension scored 3.65 (effective), and the communication dimension scored 4.33 (very effective).